KOMPLEKSITAS DAN KONTRADIKSI DALAM ARSITEKTUR : Analisa Arsitektur Vanna Venturi House - Widati, Titiani (JURNAL PERSPEKTIF ARSITEKTUR, 2023)
Robert Venturi looked at architecture from the past as case studies and established his criticisms and concepts as inspirations of the beginning of postmodern movement, at the same time they became principles and characteristics of postmodern architecture. Vanna Venturi House is one of Robert Venturi’s work where he applied his ideology, concepts and design methods. Venturi’s parameters are : pluralism, complexity and contradictions, and both and. Content analysis is the method used in the analysis to see the consistency of Venturi’s parameters in his design and to get insight on how to have the richness of meaning in architecture.